COMPUTER LINGUISTICS AS A NEW PARADIGM IN LINGUISTICS​ - Muxammadjonova Nilufar Ibroximovna (International Journal of Literature and Language Studies, 2026)
The study of language and communication has changed as a result of the quick development of digital technology. By combining linguistic theories with computational techniques and artificial intelligence, computational linguistics—also referred to as computer linguistics—has become a new paradigm in linguistic research. This multidisciplinary field makes it possible for computer systems to analyze, process, and produce natural language. With an emphasis on its theoretical underpinnings, research methodologies, and real-world applications, the current study investigates the role of computational linguistics as a new paradigm in contemporary linguistics. The evolution of computational linguistics and its impact on linguistic study were examined through a qualitative survey of academic literature. The results show that through corpus linguistics, natural language processing (NLP), machine learning, and artificial intelligence, computational linguistics has transformed language analysis. The study comes to the conclusion that computational linguistics is one of the most important paradigms in modern linguistics because it has broadened the scope of conventional linguistic inquiry and developed novel approaches to language research.